A gestão da inovação e os resultados de projetos de inovação em prefeituras paranaenses da comunidade dos municípios da região de Campo Mourão - Sampaio, Vanderlei da Silva (2018)
The general objective of this study was to analyze the relationship between the process of managing innovation projects and the results of them in prefectures of the Community of Municipalities of the Region of Campo Mourão (COMCAM). The theoretical framework of this study was structured through factors considered relevant to the subject studied and also to the respective constructs which were analyzed. The study is justified by the contribution it can make to the advance of knowledge in this area, mainly because it contributes from multiple perspectives, aiming to undertake scientific and technological progress, contributing to optimization, cost reduction, transparency, modernization, among others factors which aim for better results in the public sector. About the methodological design, the research was structured in two stages: quantitative and qualitative. In the quantitative phase, the research questionnaire was delivered to the respondents (project coordinators), in the prefectures of Paraná in COMCAM region. The sample of this study was 56 projects, in 11 prefectures of COMCAM region of Paraná. For the analysis of the data, the method of descriptive statistics and Pearson correlation were used. The qualitative step was developed, step in which all the project coordinators (respondents in the previous stage) were interviewed. This stage was structured with an exploratory-descriptive purpose, through a case study, transverse temporal perspective and level of organizational analysis. To analyze the collected data through documents and interviews with the project coordinators, we used documentary analysis, narrative analysis and content analysis. Regarding the results of the management factors of the innovation projects, it was verified which the average score was 3.80. Regarding the results of the innovation projects, it was verified that the projects presented an average score of 3.81. It was verified that the results of these research projects were positive. The main results of the research demonstrated the existence of a positive and moderate intensity relationship between the project management process and the results of these projects in the State of Paraná prefectures of COMCAM region, since the correlation coefficient was r = 0.405, value of p = 0.002. It was evidenced that when the values of the independent variable increase, so does the dependent variable, that is, the better the projects are managed, the better the results of the innovation projects. It was also identified that almost all the factors of management of innovation projects are positively correlated with results of the innovation projects, in the prefectures surveyed. Finally, the qualitative step allowed the identification of the main driving forces and inhibitors to innovation in the public sector.